Thus Spoke Uncle Sam (AmeriQuests, 2017)
This poem illustrates the path that America has been walking since its foundation by employing American political slogans that were used in the past. In this poem, Uncle Sam, a personification of the U.S. government, justifies his actions that may seem hypocritical to other countries.